Construction of a Novel Prognostic Model in Lung Adenocarcinoma Based on 7-Methylguanosine-Related Gene Signatures - Lu, Fei; Gao, Jingyan; Hou, Yu; Cao, Ke; Xia, Yaoxiong; Chen, Zhengting; Yu, Hui; Chang, Li; Li, Wenhui (Frontiers in Oncology, 2022)
Increasing evidence has implicated the modification of 7-methylguanosine (m7G), a type of RNA modification, in tumor progression. However, no comprehensive analysis to date has summarized the predicted role of m7G-related gene signatures in lung adenocarcinoma (LUAD). Herein, we aimed to develop a novel prognostic model in LUAD based on m7G-related gene signatures. The LUAD transcriptome profiling data and corresponding clinical data were acquired from the Cancer Genome Atlas (TCGA) and 2 Gene Expression Omnibus datasets. After screening, we first obtained 29 m7G-related genes, most of which were upregulated in tumor tissues and negatively associated with overall survival (OS). According to the expression similarity of m7G-related genes, the combined samples from the TCGA-LUAD and GSE68465 datasets were further classified as 2 clusters that exhibit distinct OS rates and genetic heterogeneity. Then, we constructed a novel prognostic model involving 4 genes by using 130 differentially expressed genes among the 2 clusters. The combined samples were randomly divided into a training cohort and internal validation cohort in a 1:1 ratio, and the GSE72094 dataset was used as an external validation cohort. The samples were divided into high- and low-risk groups. We demonstrated that a higher risk score was an independent negative prognostic factor and predicted poor OS. A nomogram was further constructed to better predict the survival of LUAD patients. Functional enrichment analyses indicated that cell cycle and DNA replication-related biological processes and pathways were enriched in the high-risk group. More importantly, the low-risk group had greater infiltration and enrichment of most immune cells, as well as higher ESTIMATE, Immune, and Stromal scores. In addition, the high-risk group had a lower TIDE score, and higher expressions of most immune-checkpoint–related genes. We finally noticed that patients in the high-risk group were more sensitive to chemotherapeutic agents commonly used in LUAD. In conclusion, we herein summarized for the first time the alterations and prognostic role of m7G-related genes in LUAD, then constructed a prognostic model based on m7G-related gene signatures that could accurately and stably predict the survival and guide individualized treatment decision-making in LUAD patients.